2019
DOI: 10.1159/000501518
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Allergy in Children: More than Just a Label

Abstract: Within the broad category of adverse drug reactions in children, there has been a recent focus specifically on the evaluation of children with antibiotic allergy, in particular, beta-lactam allergy. The potential consequences of being labeled beta-lactam allergy are increasingly recognized. Appropriate evaluation of children with suspected reactions to antibiotics is essential as it is increasingly being recognized that the label of “penicillin allergy” is associated with adverse health and economic outcomes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 91 publications
0
27
0
Order By: Relevance
“…On the other hand, unpredictable reactions occur in vulnerable children, unrelated to pharmacological activities actions, and are not a dose dependent. Unpredictable reactions may also be further subdivided into drug intolerance, drug idiosyncrasy, drug allergy, and pseudo-allergic reactions (13,14). Historically, the impression has been given that children are at a lower risk of ADRs than adults (15).…”
Section: Adverse Drug Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, unpredictable reactions occur in vulnerable children, unrelated to pharmacological activities actions, and are not a dose dependent. Unpredictable reactions may also be further subdivided into drug intolerance, drug idiosyncrasy, drug allergy, and pseudo-allergic reactions (13,14). Historically, the impression has been given that children are at a lower risk of ADRs than adults (15).…”
Section: Adverse Drug Reactionsmentioning
confidence: 99%
“…Data on the prevalence and incidence of antibiotic hypersensitivity reactions are limited, particularly in pediatric age and vary globally. Antibiotic allergy constitutes roughly 5-10 percent of all adverse drug reactions (13,19). It was noted that ADRs constitute a "major public health issue" in children.…”
Section: Antibiotic Allergymentioning
confidence: 99%
“…8 Avoiding mislabelling of patients with antibiotic allergy will ensure that patients are managed with the most appropriate, safe, and cost-effective antibiotic. 9,10 Until recently, it was considered unethical to challenge children with suspected antibiotic allergy in the absence of skin testing. However, two recent studies, 11,12 including one performed in Canada, 11 cast doubt on the utility of this guideline as they suggest that challenges, but not skin testing, are essential to the appropriate diagnosis of antibiotic allergy.…”
Section: Introductionmentioning
confidence: 99%
“…13 Understandably, correctly diagnosing antibiotic allergy is important as it mitigates the potential for adverse health outcomes and financial costs. 9 Despite these factors, antibiotic challenges are not routinely performed and families are often inappropriately burdened by a misdiagnosis. Moreover, the impact of being delabelled subsequent to a passed challenge remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Oral challenge tests are considered to be the gold standard to establish or exclude drug hypersensitivity[72]. According to a low frequency of hypersensitivity it is recommended that a graded challenge is performed in the context of a low likelihood of drug allergy[72,73]. Several studies about cross reactivity in this drug group have suggested that the overall risk is low given the differences in size of the lactone ring[74].…”
mentioning
confidence: 99%